ANALISIS YURIDIS PUTUSAN MAHKAMAH AGUNG TERHADAP KASUS TINDAK PIDANA PENCEMARAN NAMA BAIK (Studi Putusan Mahkamah Agung Nomor 1845/K/Pid/2009) - Paramartha, I Gede Raditya Chandra; hartono, made sugi; setianto, muhamad jodi (Jurnal Ilmu Hukum Sui Generis, 2024)
In cases of criminal defamation. Often the indications in criminal acts of defamation cannot be produced and the verdict is regardless of their existence so that many people view this as unfair. This research was intended to analyze and obtain an overview of how defamation decisions are created and to find out how judges consider when making defamation decisions, in this case the Supreme Court Decision Number 1845 K/Pid/2009. This research applies a type of normative juridical research, using the Legislative Approach, and Case Approach using primary, secondary and tertiary legal material collection techniques. The analysis carried out is qualitative analysis. Based on the results of this research, firstly, the application of Article 310 paragraph (1) of the Criminal Code is appropriate and has fulfilled all the elements in that article. The judge really studied the case and had a broad perspective by considering both juridical and non-juridical facts, so that the resulting decision could be said to have created justice. However, from the other side, the author observes that there are other elements that influence the judge's considerations, including: (1) Intention/Background of the Defendant's actions, (2) The Defendant spreads slander via SMS. So from the analysis that has been carried out, defamation is considered as a reason. The justification in this case is appropriate and correct, and is also appropriate so that it does not violate the law or positive law.